(untitled) (Socio-economic relations in the digital society, 2019)
Modern economic development of Ukraine is inseparably linked with investment processes that are the driving force behind economic integration into the world economy through the renewal of fixed assets, transfer of capital from one to the other spheres, technology transfer, innovation and management experience. The article analyzes dynamics of development of foreign direct investment in Ukraine in the period from 2002 to 2016. Correlation of investment with GDP in the national and foreign currency and considers the problems hampering improvement of the investment climate of the country. Based on the offi cial data on the level of investment and GDP, we can conclude that despite the growing level of FDI in international currency and an eff ective investment policy, living standards of the population still remains low and even declined during the last year.